Garment industry in Lithuania: a study of self-reported dermatological problems - Naruševičiūtė-Skripkienė, Edita; Moskalionė, Beatričė; Audickaitė, Aistė; Grigaitienė, Jūratė; Bylaitė-Bučinskienė, Matilda (Acta medica Lituanica, 2015)
Background. According to our knowledge, there are no official medical statistics about skin problems of Lithuanian textile workers. The aim of the study is to evaluate work related skin problems in this occupational field, their character, and what alterations if any can be carried out. Materials and methods. A self-reported anonymous survey was carried out in 12 randomly selected textile factories from 6 cities of Lithuania in 2013–2014. Data were analyzed by SPSS v21.0. Results. 91% of all the employees (551) were females with the mean experience in textile industry of 14.2 years (SD 7.2). The majority (63%) of the respondents were sewing machine operators. The most commonly mentioned risk factors were textile (89.7%) and dust (36.8%) containing different chemical substances that we did not analyze in our study. 83.1% of the respondents had no air conditioning systems at their working place. Atopic skin diseases were declared by 165(30%) workers. 208(37.7%) participants complained about skin problems. Dermatological treatment was received by 190(91.4%) respondents (topical corticosteroids, antibiotics and emollients) and was effective in 74.7% of all cases. Almost all of the respondents (97%) declared having no training about occupational skin problems and skin protection measures during apprenticeship, though 59% of them pointed out it would be desirable. Still, the usage of emollients at work is rather high – 76.6%. Conclusions. Our study highlighted that improvement is needed in pre-occupational councelling and working conditions.